Newly synthesized carbocyanine fluorescent probes, their characteristics and behavior in proliferating cultures - Goncharuk, E.I.; Borovoy, I.A.; Pavlovich, E.V.; Malyukin, Yu.V.; Grischenko, V.I. (Вiopolymers and Cell, 2009)
Aim. To study possibile application of C2, C9, C18 and JC-1 carbocyanine fluorescent dyes for cell culture characterization. Methods. Morphological methods, fluorescence-activated cell sorting (FACS) analysis, luminescent microscopy were used. Results. The studied carbocyanine probes were shown to be preserved in dividing cells for at least 4 duplications. It was found that carbocyanine probe JC-1 did not transit from cell to cell under combined culturing of labeled and non-labeled cells. Conclusions. The paper covers the use of carbocyanine fluorescent probes for long-term culturing of cell lines. Probes C9 and JC-1 were optimal for the proliferative culture observation, allowing to trace mitochondrial functional state.